Developing an Oral-Insulin-Delivery System using GET-peptide-mediated transcytosis - Rehmani, Sahrish (2021)
Insulin a peptide hormone regulates blood glucose levels and is considered a mainstay of treatment for diabetic patients. Oral insulin delivery still represents an overwhelming challenge due to its physio-chemical instability in gastro-intestinal tract (GIT) and poor intestinal permeability. A novel multidomain fusion-peptide system was employed to overcome these barriers termed Glycosaminoglycan (GAG)-binding enhanced transduction (GET) system, where GAG-binding motif promotes cell targeting and surface binding, whereas cell-penetrating-peptides (CPPs) region allows efficient cell entry. Here, potential of GET system in enhancing intestinal insulin permeation (transcytosis and translocation efficiency) was assessed across an in-vitro gut model system (Caco-2 cell monolayers). Insulin recycling was studied using different secretion regulators, moreover functional activity (by employing insulin-reporter cells) and stability of insulin-GET nanocomplexes (NCs) was also determined. In-house synthesised NHS-Fluorescein labelled insulin (Ins-F, non-quenchable) was used for studying internalisation, and transcytosis. Different stability assays were developed for GET system and insulin-GET NCs using quenchable proprietary FITC-insulin (Ins-F*). The difference in fluorescent behaviour of both insulins was studied using quenching and dequenching assays. pH-sensitive micro-particulates (MPs) based on Eudragit-L100 served as an enteric carrier system for insulin-GET NCs. These Eudragit-L100-MPs were characterised for their size, charge, morphology, drug release as a function of pH, and cellular uptake efficiency of released NCs across Caco-2 monolayers. Furthermore, enteric coated minicapsules were developed as an alternative to MPs for oral insulin delivery. GET-peptide generates NCs with insulin and efficiently enhances its transport across differentiated model of intestinal epithelium (>8.7-fold greater translocation efficiency over un-modified insulin). Both the GET-system and insulin-GET NCs were resistant to proteolytic degradation, and NCs were stable and stayed intact even after being translocated inside cells. GET-peptide quenched the fluorescence of Ins-F*, which was successfully reversed using different proteolytic enzymes. Various studied inhibitors had insignificant effect on transcytosis and cellular uptake of NCs. Functional assessment using transcription reporter assays activated by insulin signalling (iLite-cells) revealed that NCs retain biological activity and may induce pharmacological response. Spherical Eudragit-L100-MPs (diameter 1250 nm & surface potential -8.3mV) displayed an entrapment efficiency of 77%. These MPs prevented insulin release at pH 1.2, with maximum release observed at pH 7.4. Likewise, enteric-coated minicapsules exhibited pH-dependent release in biorelevant media providing complete release in FaSSIF. The ability of this multidomain peptide sequence (GET) in promoting insulin permeation, transcytosis and intracellular uptake across in-vitro intestinal model while retaining insulin's functional activity might provide a step forward towards development of on oral insulin delivery system. Overall, this work underlines the application of non-viral vectors to overcome gastrointestinal barriers associated to oral insulin delivery. Current focus is to improve insulin bioavailability by formulating novel carrier system, which may possibly allow GET peptides to be an alternative approach in establishing effective oral peptide therapeutics for diabetes.